Comparative Review of Science Teachers’ and Prospective Science Teachers’ Awareness, Efficacy and Attitudes and Opinions towards STEM - Şeyma Nur Gülpinar; Selda Bakir (Universitas Pendidikan Indonesia, 2023)
This research aims to compare the awareness, efficacy and attitudes, and opinions of science teachers (STs) and prospective science teachers (PSTs) toward STEM. In this study, convergent parallel design from mixed methods was used. The study group consists of 45 STs and 177 PSTs. In the quantitative dimension of the study, “Teacher Efficacy and Attitudes Towards STEM Survey” and “STEM Awareness Scale ” were applied to the study group, which was formed by sampling criteria and maximum diversity from purposeful sampling. In the qualitative dimension of the research, semi-structured interviews were conducted with 24 STs and 25 PSTs selected through maximum diversity sampling from purposeful sampling. As a result of the research, it was observed that although the STEM awareness, efficacy, and attitudes of STs and PSTs were similar, they had positive attitudes. However, most of the participants in both groups considered themselves inadequate in STEM, expressed their opinions about the adverse effects of STEM applications as well as their positive effects, and that STEM applications were effective in career selection and country development.